Oxygen and ozone - Battino, Rubin (Solubility data series, 1981)
Oxygen and Ozone deals with the solubility of oxygen and ozone in pure liquids, liquid mixtures, aqueous and organic solutions, biological fluids, and some miscellaneous solvents and mixtures. The coverage is on gas/liquid systems at high and low pressures. Individual data sheets for each gas/liquid system are included. This volume consists of three sections and begins with an introduction to the solubility of gases in liquids, with emphasis on the solubility of oxygen in water at atmospheric pressure. Oxygen solubilities up to and above 200 kPa (2 bar) in media such as water, hydrocarbons, or.